Potencialidades e limitações do enfoque ciência, tecnologia e sociedade no ensino de eletricidade nos anos finais do ensino fundamental - Caporal Filho, Ricardo Goulart (2017)
The present study reports a pedagogical proposal that aims to evaluate the use of the Science,Technology and Society (CTS) approach in Science Teaching (electricity) in the final years of Elementary School. The study is a dissertation presented to the Postgraduate Program in Teaching Science and Mathematics (PPGECM) of the University of Passo Fundo (UPF), within the Theoretical-methodological Foundations for the teaching of Science and Mathematics research line. The objectives of this study are to elaborate a proposal for the teaching of electricity contents using the CTS approach in Elementary School and to evaluate the challenges and potentialities of this approach in science teaching. In this sense, we use the theoretical foundation of the Three Pedagogical Moments organized by Demétrio Delizoicov and collaborators who translated the educational perspectives of Paulo Freire, adapted to the Teaching of Sciences. In order to develop this research we created a didactic sequence (educational product) addressing the basic contents of static electricity, attraction and repulsion of charges, electric current, potential difference and transformations of different forms of energy (mechanical, solar, wind, thermal , nuclear and biomass) in electric energy. In order to arouse the greatest interest and encourage the students' active participation in class, a variety of didactic materials were designed and constructed using alternative materials, especially static electricity generators, electroscopes, dynamos and scale models, illustrating the different ways of obtaining electricity. Throughout the meetings, diverse pedagogical strategies were used, such as: Presentation and discussion of didactic videos; Practical experiments; Workshop for analysis and discussion of a possible form of energy generation based on Role-Playing Game; Media production by students (folder); Use of computer science in applied research; Computer simulations and educational software in the visualization and understanding of electrical phenomena. The proposal was put into practice in the Municipal School of Sagrado Coração de Jesus with ninth grade students of the Final Years of Elementary School in the city of São Borja, Rio Grande do Sul. Data collection and evaluation of the study were used as well as the following research tools: initial questionnaire, final questionnaire and daily record forms. In both instruments a Content Analysis was performed according to the assumptions of Bardin of the textual productions of the participants. The results made it possible to infer that, at the end of the application of the proposal, students presented a critical position when asked about the waste in the consumption of electric energy, we still identified positive signs of appropriation, or evolution, in the fixation of the studied knowledge in the didactic sequence, with additions of critical sensitization, active and emancipatory participation of students (CTS appropriation).